PENGARUH FAKTOR-FAKTOR MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Silva Yuni Prasetya Kasma; Moh Nasikh (Jurnal Akademika, 2021)
This study aims to develop a research model that studies whether the variables of the marketing mix affect consumer purchasing decisions through perceived value in Supermarkets Rejeki Baru Malang. The analysis method uses multiple regression  with software. Sampling was 69 respondents from Rejeki Baru Supermarkets taken within 1 day.The results showed that the four marketing mix variables had a positive and significant effect on the value of consumer perceptions, namely the product variable 0.445, the price of 0.212, the distribution of 0.407, and promotion of 0.138 were not significant in influencing the value of consumer perceptions. Product variable is the dominant variable in influencing the perceived value of consumer purchases with a significant level of 0.445. Perceived value of consumer purchases has a significant positive effect on consumer shopping decisions Rejeki Baru Malang. Keyword: marketing mix, product, price, promotion, distribution, buying